Interlocução entre escola e família: aplicativo em dispositivo móvel como proposta de mediação para um ambiente de comunicação, interação e colaboração - Dallanora, Geferson Durigon (2023)
The present dissertation, developed in the Graduate Program in Networked Educational Technologies of the Federal University of Santa Maria (UFSM), specifically in the line of research of Development of Networked Educational Technologies, addresses as its central theme the relation of dialogicity between School and Family represented through a collaborative pedagogical practice. For the development of the research, an exploratory investigation was used, with a qualitative approach, and the methodology adopted is the action research proposed by Thiollent (1986). The research problem, therefore, is configured through the following question: how does an interactive and shared digital School Journal on a mobile device contribute to the school community by bringing the family closer to the school? The objective is to analyze the contributions of a digital School Journal, shared on a mobile device, to bring the school community closer through an environment focused on interaction, collaboration and reflection. The following techniques were used for data collection: meeting summaries, observations and notes made by the researcher, field diaries, narrative rescues and group opinions. The collection of qualitative data improves and clarifies the results presented in the research carried out with the community of Escola Básica Estadual Érico Veríssimo in Santa Maria, Rio Grande do Sul. articulation with educommunication practices and educational technologies in a network, provide important elements for the creation of an integrative and collaborative environment. And that dialogue relationships in communicative ecosystems enable the construction and reconstruction of knowledge collectively. With the creation of the Jornal Educom application as a pedagogical product, it is estimated to expand the moments of dialogue with the school community in the debate on social themes of common interest.